Medio de comunicación digital aldia.com.ec y su influencia en el desarrollo de la cultura de los moradores del sector los rosales en el cantón Quevedo - Zamora Castillo, Iliana Elibeth (2017)
This research work has as a specific objective a program of cultural information in the digital medium. Aldia.com.ec for technology purposes. The roses in the canton quevedo, acquires and learns many of the knowledge about culture. In Ecuador, the Organic Law of Communication was established with the sole purpose of respecting rights, the way of disseminating information and supporting access to different media such as radio, television, and print media. The digital media nowadays are very used by the people since they help to be informed in an updated and fast way, allowing to obtain information of what happens in different parts of the world and at a low cost. Several methods were used to elaborate the investigation. A questionnaire of questions was used, statistical graphs, these method made feasible the study of relation of the variables to verify the validity of the problem. It was concluded that the program of cultural information in the digital medium is of great help for the residents of the Los Rosales sector, since they will acquire many values and customs knowledge that will improve their behavior and way of life.